2008
DOI: 10.1080/02652030701598694
|View full text |Cite
|
Sign up to set email alerts
|

NovaSil clay intervention in Ghanaians at high risk for aflatoxicosis: II. Reduction in biomarkers of aflatoxin exposure in blood and urine

Abstract: The efficacy of NovaSil clay (NS) to reduce aflatoxin (AF) biomarkers of exposure was evaluated in 656 blood samples and 624 urine samples collected from study participants during a 3-month phase IIa clinical intervention trial in Ghana. NS was delivered before meals via capsules. Serum AFB (1)-albumin adduct was measured by radioimmunoassay and urinary AFM (1) metabolites were quantified by immunoaffinity-high-performance liquid chromatography (HPLC)-fluorescence methods. Levels of AFB (1) -albumin adduct in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 44 publications
3
64
1
2
Order By: Relevance
“…Moreover, the results of this study support the application of NS for the management of aflatoxicosis in humans who are acutely exposed to high levels of dietary aflatoxins. Additional results from this study indicate that ingestion of capsules containing an MED of NS, significantly reduce biomarkers of aflatoxin exposure in the blood and urine from study participants (Wang et al 2007). Further studies are planned to optimize the dosimetry and delivery methods for NS clay.…”
mentioning
confidence: 97%
“…Moreover, the results of this study support the application of NS for the management of aflatoxicosis in humans who are acutely exposed to high levels of dietary aflatoxins. Additional results from this study indicate that ingestion of capsules containing an MED of NS, significantly reduce biomarkers of aflatoxin exposure in the blood and urine from study participants (Wang et al 2007). Further studies are planned to optimize the dosimetry and delivery methods for NS clay.…”
mentioning
confidence: 97%
“…38,[41][42][43] Human intervention trials with NS products in Texas and Ghana have also reported a similar reduction of AF bioavailability, resulting in as much as a 58% decrease in biomarker levels. 44,45 Recently, the NS parent compound was refined, producing a product that is more uniform in particle size, with the majority of the particles residing in the 45-to 100-μm range. The new product, Uniform Particle Size NovaSil (UPSN), displayed a similar AFB 1 sorption capacity to that of NS during isothermal analysis and was deemed to be more palatable for human consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in this district showed high exposure rates of aflatoxins with 100% of people (n=180) screened testing positive for the AFB 1 -albumin biomarker of exposure and 75% testing positive for urinary biomarkers of exposure. 15 Thirty-six mothers who were trained by the Nutrition Department of the Ejura-Sekyedumase District hospital on weanimix preparation were recruited and consented for their participation in the study. Study participants were from the following three communities in the district, Hiawoawu, Dromankuma and Ejura town.…”
Section: Methodsmentioning
confidence: 99%